Local sharing in Gothenburg: An investigation of promising districts and proposal of sharing initiatives - Li, Xiaoxia (My University, 2021)
Sharing economy is attracting more and more attention worldwide in the last decade. Local sharing economy that contributes to increase the duration of the consumed household items is gradually regraded as an effective solution to the promotion and adaption of urban sustainable development. The thesis aims to support city planners in investigating the potential of the sharing strategies at the local level, the case study of Gothenburg city was investigated with respect to the determination of the promising sharing areas and the proposals of sharing initiatives. The modifications of SEsam were used to illustrate the patterns of consumption and willingness of participating in the sharing economy for both the household archetypes and neighborhood areas in Gothenburg. The consumption patterns present that the clothes occupy the largest consumption in quantities, followed by the equipment and hobbies which is the second largest. The tools, vehicles, equipment and hobbies are the top three categories that people in Gothenburg show the most interest in participating in the sharing economy as both users and providers as observed in willingness patterns. Besides, similar geographical distributions are observed between the consumption and willingness patterns. Based on the consumption and willingness patterns, the results of clustering analysis suggest that the neighborhood type C composed of only five centrally positioned districts should be regarded as the promising sharing areas as it is characterized by overall highest consumption and willingness patterns compared with the other clusters. Sharing initiative library coupled with the filter (the smart Map) was applied to assist in proposing the sharing initiatives in the districts of neighborhood type C. It reveals that all sharing categories should be considered, however, various priorities should be given, clothes sharing is of the most importance for instance. Nonetheless, it is suggested that that the selection of the specific sharing initiatives of sharing sectors should be further evaluated under the local context.
Keywords: Environmental impacts; Gothenburg City; Household consumption; Sharing economy; Willingness of participation